2015
DOI: 10.17554/j.issn.2224-3992.2015.04.531
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinones as Possible Therapeutic Agents for Cardiovascular, Cerebral, Hepatic, and Bone Diseases

Abstract: The root of Salvia miltiorrhiza (Tan shen) has been used as a traditional drug for circulatory disorders including ischemic diseases such as angina pectoris. Effective components protecting the myocardium against ischemia-induced metabolic disturbances; tanshinone IIA, tanshinone I, tanshinone V, tanshinone VI, and dihydrotanshinone were isolated. Among them, we found tanshinone VI as the most effective and possible agent with cardioprotection against ischemia/reperfusion injury in Langendorff manner by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several phenathro [1,2-b]furan-10,11-dione and phenathro [4,3-b]furan-4,5-dione derivatives isolated from the dried roots of Salvia miltiorrhiza Bunge (red sage), a herb native to China and Japan, or Salvia glutinosa (glutinous sage), a herbaceous perennial native to Central and East Europe and West Asia, [1][2][3][4][5] display many biological activities, including antitumor activity. [6][7][8][9][10][11][12][13][14] Syntheses [15][16][17][18][19] and biological evaluations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] of these compounds have remained a challenging field of research for the last few decades. In our earlier work, we showed that β-furyl α,β-unsaturated aldehydes 20 can be used in the synthesis of furophenanthroquinones 21 that simulate the ABCD rings of tanshinone I, a compound with great potential for the treatment of breast cancer, 6 and as well as several polynuclear aromatic hydroxy compounds.…”
mentioning
confidence: 99%
“…Several phenathro [1,2-b]furan-10,11-dione and phenathro [4,3-b]furan-4,5-dione derivatives isolated from the dried roots of Salvia miltiorrhiza Bunge (red sage), a herb native to China and Japan, or Salvia glutinosa (glutinous sage), a herbaceous perennial native to Central and East Europe and West Asia, [1][2][3][4][5] display many biological activities, including antitumor activity. [6][7][8][9][10][11][12][13][14] Syntheses [15][16][17][18][19] and biological evaluations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] of these compounds have remained a challenging field of research for the last few decades. In our earlier work, we showed that β-furyl α,β-unsaturated aldehydes 20 can be used in the synthesis of furophenanthroquinones 21 that simulate the ABCD rings of tanshinone I, a compound with great potential for the treatment of breast cancer, 6 and as well as several polynuclear aromatic hydroxy compounds.…”
mentioning
confidence: 99%